A SEMIOTIC ANALYSIS OF ROLAND BARTHES ON OLIVER GOLDSMITH'S DRAMA TEXT SHE STOOPS TO CONQUER - Multazam Abubakar (Universitas Hasanuddin, 2026)
This study aims to identify the denotative, connotative, and mythical meanings in selected dialogues and examine the social and cultural ideologies they represent. Using a qualitative textual analysis approach, five purposively selected dialogues were analyzed based on Barthes' three levels of signification: denotation, connotation, and myth. The findings show that the dialogues construct and naturalize ideologies related to tradition and modernity, popular culture, social hierarchy, class privilege, and gender morality. At the denotative level, they depict ordinary interactions. At the connotative level, they convey meanings associated with identity, power, and morality. At the mythic level, they both reinforce and challenge cultural assumptions in eighteenth-century England. Through irony, humor, and mistaken identity, Goldsmith critiques social distinctions and the ideological foundations of class and gender relations.